2014
DOI: 10.1155/2014/561459
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammatory and Anti-Inflammatory Cytokines in the Pathogenesis of Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common chronic disease of human joints. The basis of pathologic changes involves all the tissues forming the joint; already, at an early stage, it has the nature of inflammation with varying degrees of severity. An analysis of the complex relationships indicates that the processes taking place inside the joint are not merely a set that (seemingly) only includes catabolic effects. Apart from them, anti-inflammatory anabolic processes also occur continually. These phenomena are dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
1,189
1
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,241 publications
(1,240 citation statements)
references
References 217 publications
(228 reference statements)
40
1,189
1
10
Order By: Relevance
“…These studies have demonstrated the enhanced production of key inflammatory mediators from chondrocytes exposed to OA synovial fluid or the synovium itself, which may act to further stimulate macrophage inflammation. 12,56,57,68,69 Cumulatively, our results agree well with changes seen in early OA and with similar in vitro model systems using NCs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These studies have demonstrated the enhanced production of key inflammatory mediators from chondrocytes exposed to OA synovial fluid or the synovium itself, which may act to further stimulate macrophage inflammation. 12,56,57,68,69 Cumulatively, our results agree well with changes seen in early OA and with similar in vitro model systems using NCs.…”
Section: Discussionsupporting
confidence: 88%
“…Each of these enzymes and inflammatory cytokines has been shown to be increased in OA. 5,12,56,57 These results demonstrate significant initial phenotypic differences between the NCs and OACs before coculture with macrophages.…”
Section: Initial Chondrocyte and Macrophage Phenotype Before Coculturementioning
confidence: 62%
“…Salidroside treatment was found to decrease expression of TNF-α, and IL-6, which further supports our hypothesis. IL-1 β has been proposed as the key cytokine involved in the pathogenesis of osteoarthritis, because it induces inflammatory reactions and catabolic effects independently as well as being combined with other mediators with respect to the articular cartilage and other elements of joints [28]. In this study we observed that salidroside treatment significantly decreases expression of IL-1 β an excellent anti-inflammatory property of salidroside.…”
Section: Discussionsupporting
confidence: 55%
“…Osteoarthritis (OA) is the most common form with increased prevalence in the aged population and characterized by progressive degeneration of articular cartilage, aberrant chondrocyte maturation, and osteophyte formation in subchondral bone, resulting in remodeling and functional loss of the joint (Zhang and Jordan 2010). Proinflammatory cytokines (TNF-a, IL-1) and matrix metalloproteinases (MMPs) play central roles in OA (Lories and Luyten 2005;Wojdasiewicz et al 2014). Elevated BMP-2 expression was found in articular chondrocytes of OA mouse models (Blaney Davidson et al 2006).…”
Section: Dysregulation Of Tgf-b or Bmp Signaling In Catabolic Bone DImentioning
confidence: 99%